Job specification from the stakeholders’ perspective: the security guard’s case - Contreras-Pacheco, Orlando Enrique; Reyes-Rodríguez, Juan Felipe; Martínez-Ardila, Hugo Ernesto (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Starting from the identification of necessary requirements for a position, the purpose of this study is to propose the design of the generic job specification of a security guard. To do this, a qualitative research of a deductive nature is designed, based on data collection through semi-structured interviews. The field work is carried out on 22 representatives of the interested parties of security guard work in the northeast of Colombia. Subsequently, through a direct approach content analysis, a structured approach to the respective profile is obtained. The study finds that the requirements of the security guard job transcend the basic knowledge and skills in regulations, attention and handling of weapons, since it is essential to have a tendency towards a scrupulous personality, in addition to requiring a series of specific emotional aptitudes to perform appropriately the respective work.